Telecommunications and information services for the poor : toward a strategy for universal access - Navas-Sabater, Juan (World Bank WashingtonUS, 2002)
Explores the role of information and communications technologies (ICTs) in narrowing the digital divide. Outlines policies, regulatory measures, and targeted investments that the World Bank Group can promote through its operational work in the ICT sector, for improved impact in countries' efforts to reduce poverty.